2013
DOI: 10.1021/nn404353w
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Polypyrrole/Iron Oxyhydroxide Hybrid Nanoparticles for Chemical Nerve Gas Agent Sensing Application

Abstract: Multidimensional FeOOH nanoneedle-decorated hybrid polypyrrole nanoparticles (PFFs) were fabricated using dual-nozzle electrospray and heat stirring process. To decorate metal oxide nanoneedles on the polypyrrole (PPy) surface, metal oxide particle-decorated PPys (E_PPy) were fabricated as starting materials. The E_PPy particles were prepared by dual-nozzle electrospray because ferric ions (Fe(3+)) dispersed on the surface reacted with hydroxide (OH(-)) ions in the collector solution without aggregation of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 45 publications
0
44
0
2
Order By: Relevance
“…Gaury et al (2013) prepared Nb-doped WO 3 thin films by electrospraying a tungsten isopropoxide in 2-propanol precursor solution on glass substrates for potential use in gas sensors. In a different study, Lee et al (2013) fabricated polypyrrole/iron oxyhydroxide hybrid nanoparticles using co-axial electrospray and heat stirring process for nerve gas sensing applications. Their most recent study demonstrated the production of urchin-like polypyrrole nanoparticles with various diameters using co-axial electrospray and vapor deposition polymerization (Lee et al, 2014).…”
Section: Applicationsmentioning
confidence: 99%
“…Gaury et al (2013) prepared Nb-doped WO 3 thin films by electrospraying a tungsten isopropoxide in 2-propanol precursor solution on glass substrates for potential use in gas sensors. In a different study, Lee et al (2013) fabricated polypyrrole/iron oxyhydroxide hybrid nanoparticles using co-axial electrospray and heat stirring process for nerve gas sensing applications. Their most recent study demonstrated the production of urchin-like polypyrrole nanoparticles with various diameters using co-axial electrospray and vapor deposition polymerization (Lee et al, 2014).…”
Section: Applicationsmentioning
confidence: 99%
“…Recently, some groups have developed gas sensors based on various metal-oxides for onsite monitoring of DMMP vapor [1][2][3][4][5][6][7]. These metal-oxide-based sensors offer advantages such as low cost, fast response time, ease in manufacturing, small size, high efficiency, low power consumption, and portability.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of the CoMoO 4 NWs, PPy and CoMoO 4 /PPy hybrid nanocomposite have been evidently revealed by XRD analytical patterns in Figure 4a. 39 In the red part, one significant diffraction peak at around 26° was observed, resulting from the CoMoO 4 core and PPy shell.aa The coreshell structure CoMoO 4 /PPy hybrid nanocomposite is observed to display all the characteristic peaks corresponding to CoMoO 4 and PPy separately, confirming free of impurities phases in the nanocomposites. 21-0868), demonstrating the lattice parameters observed are well matching the PDF card.…”
Section: Resultsmentioning
confidence: 81%